2015
DOI: 10.3945/ajcn.114.105395
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fish intake on vitamin D status: a meta-analysis of randomized controlled trials

Abstract: Results: Seven articles and 2 unpublished study data sets with 640 subjects and 14 study groups met the inclusion criteria and were included in this meta-analysis. Compared with controls, the consumption of fish increased 25(OH)D concentrations, on average, by 4.4 nmol/L (95% CI: 1.7, 7.1 nmol/L; P , 0.0001, I 2 = 25%; 9 studies).The type of the fish also played a key role: the consumption of fatty fish resulted in a mean difference of 6.8 nmol/L (95% CI: 3.7, 9.9 nmol/L; P , 0.0001, I 2 = 0%; 7 study groups),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 50 publications
4
50
0
Order By: Relevance
“…One possible explanation for this finding is that a major source of omega-3 fatty acids is seafood, some types of which also contain high levels of TMAO (Zhang et al, 1999). Strengthening this hypothesis, we found that both mercury and vitamin D levels, which are known to increase with consumption of certain fish (Bradley et al, 2017;Lehmann et al, 2015), were also significantly positively correlated with TMAO levels (r = 0.11, r = 0.13, respectively; p < 0.05). In addition, we found that interleukin-8 was significantly positively correlated with TMAO (r = 0.16, p < 0.005).…”
Section: Tmao Is Associated With Nutrition Inflammation and Blood Psupporting
confidence: 62%
“…One possible explanation for this finding is that a major source of omega-3 fatty acids is seafood, some types of which also contain high levels of TMAO (Zhang et al, 1999). Strengthening this hypothesis, we found that both mercury and vitamin D levels, which are known to increase with consumption of certain fish (Bradley et al, 2017;Lehmann et al, 2015), were also significantly positively correlated with TMAO levels (r = 0.11, r = 0.13, respectively; p < 0.05). In addition, we found that interleukin-8 was significantly positively correlated with TMAO (r = 0.16, p < 0.005).…”
Section: Tmao Is Associated With Nutrition Inflammation and Blood Psupporting
confidence: 62%
“…Many investigations, as highlighted by the meta-analysis by Lehmann et al [69], indicate that fish consumption contributes to total vitamin D intake. Vitamin D is involved in neuromuscular function and is essential for maintaining calcium and phosphate homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the active form of vitamin D binds to a highly specific nuclear receptor in the muscle tissue [64,68] and leads to protein synthesis and growth of muscle tissue [64]. Weekly fatty fish consumption significantly increases vitamin D levels [69]. A study carried out by Lu et al [65] showed wild salmon as having the highest vitamin D3 content, while the farmed fish exhibited a 25% reduction in the content of vitamin D3.…”
Section: Fish Consumption Increases Vitamin D Levelsmentioning
confidence: 99%
“…Simulating fish intake according to the guidelines (40 g/day) resulted in a relatively small contribution to vitamin D intake (∼10-15% of the recommended intake) that would not be sufficient to reach the recommended intake of 10 µg/day. Similarly, a recent meta-analysis on the potential of fish to improve serum vitamin D status concluded that fish consumption (∼42 g/day over 4 weeks) increased the concentration of 25(OH)D, but it was not enough to achieve an optimal vitamin D status [15]. Thus, to attain higher intakes of vitamin D, it is necessary to consume fatty fish more than once per week.…”
Section: Discussionmentioning
confidence: 99%
“…With the new recommended vitamin D intake of 10 µg/day, it is evident that a major part of the population will fall short of this intake level. Earlier studies investigated the importance of different dietary sources to population intakes of vitamin D [14,15], whereas others addressed the potential contribution of fortification of common foods with vitamin D [16,17,18]. These studies concluded that vitamin D intake was too low to sustain a healthy vitamin D status in the population without mandatory fortification of staple foods or without a dramatic increase in fish consumption.…”
Section: Introductionmentioning
confidence: 99%